2017
DOI: 10.1002/jclp.22455
|View full text |Cite
|
Sign up to set email alerts
|

Brightening the Day With Flashes of Positive Mental Imagery: A Case Study of an Individual With Depression

Abstract: This article presents a case example of an individual with current major depression engaging in a positive mental imagery intervention, specifically a computerized cognitive training paradigm involving repeated practice in generating positive imagery in response to ambiguous scenarios. The patient's reported experience of the intervention suggests the potential of the positive imagery intervention to “brighten” everyday life via promoting involuntary “flashes” of positive mental imagery in situations related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…Previous reports of the effect of positive (visual) imagery training showed that depressed individuals associate their improvement with involuntary positive images accompanied by “bursts of positive affect” after imagery training (Blackwell & Holmes, ). Moreover, positive imagery training results in brain changes of medial prefrontal regions (also involved in positive core feelings) associated with pleasantness ratings of imagined situations (Murphy et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports of the effect of positive (visual) imagery training showed that depressed individuals associate their improvement with involuntary positive images accompanied by “bursts of positive affect” after imagery training (Blackwell & Holmes, ). Moreover, positive imagery training results in brain changes of medial prefrontal regions (also involved in positive core feelings) associated with pleasantness ratings of imagined situations (Murphy et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…It would also be useful for a future RCT to include a longer follow-up period, including diagnostic assessments at follow-up. Additional finer-grained mechanisms measured, for example, momentary assessment of affect [ 76 ] or positive imagery in everyday life [ 77 ], would also be helpful to build a more comprehensive picture of potential mechanisms. In the current feasibility study, details of the treatment-as-usual received by each individual participant during their participation in the study (e.g., number and nature of psychotherapy sessions received, if any) is not collected, but such information would be useful to collect in future trials where possible.…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals who want to decrease long‐term participation restriction should consider screening patients with knee OA for low positive affect and high negative affect. Previous research studies have identified strategies for improving affect states that might be effective in this population, such as positive psychology interventions , which are low cost and can be self‐administered. In a recent randomized controlled trial, Taylor et al found that participants who engaged in “positive activity” exercises (e.g., positive mental imagery, performing acts of kindness, or expressing gratitude) saw greater improvements in positive affect and greater decreases in negative affect than the control group .…”
Section: Discussionmentioning
confidence: 99%